IMPLEMENTATION OF INCLUSIVE EDUCATION: CHALLENGES AND STRATEGIES FOR RELIGIOUS EDUCATION FOR PEOPLE WITH DISABILITIES - Bariroh, Fina Wilda; Wahid, Abd Hamid; Agus R, Abu Hasan (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to explore the implementation of inclusive education in the context of religious education, especially at the Sabilillah Inclusion Islamic Boarding School, as well as identifying the challenges and strategies implemented to achieve it. The method used in this research is a qualitative approach with a case study at the Sabilillah Inclusion Islamic Boarding School. Data was obtained through interviews with the head of the Islamic boarding school, administrators, teachers and the surrounding community, as well as direct observation of the learning process and available facilities. The research results show that inclusive education at the Sabilillah Inclusion Islamic Boarding School is implemented with an approach that prioritizes equality and respect for differences. This Islamic boarding school provides equal opportunities for all students, including those with disabilities, to obtain quality religious education. However, the main challenges faced are the readiness of educators who are not sufficiently trained to manage inclusive classes, limited disability-friendly facilities, and the social stigma that still exists in society. This Islamic boarding school seeks to overcome these challenges by providing more accessible facilities, teaching tailored to individual needs, and using technology as a learning tool. This research concludes that inclusive religious education at the Sabilillah Inclusion Islamic Boarding School has succeeded in creating a more open and friendly learning environment for all students, although there are still several aspects that need to be improved. Community support and sustainable infrastructure development are very important to ensure the success of more optimal inclusive education.